SAINS DAN TEKNOLOGI DALAM AL-QUR'AN (FENOMENA MAKROKOSMOS DAN MIKROKOSMOS) - Siti Romlah Siti Romlah (Universitas Yudharta Pasuruan, 2017)
Human thinking in the world of science had been held from the time BC to the modern times, it progresses more rapidly with technology is very advanced, though the truth of science that has been invented by man through his thinking is still a relative, therefore prone to conflicts between the one with others, some are contrary to its holy book, there are senergis with its holy book, even among science, bebil and the Qur'an. Sain is derived from the English